Depression study with canonical correlation analysis - Izzat Fakhruddin Kamaruzaman, 1990- author; Robiah Adnan, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2014